Gallbladder-warming Decoction with Bupleurum and Scutellaria inhibits Anxiety and Depression of Rats. Issue 2 (February 2020) - Sun, Ning; Ren, Yumei; Wang, Mingyu; Miao, Xinyan; Meng, Zhiyong; Wang, Chaobo; Yuan, Xiaolong; Wang, Liang; Fu, Chen; Zhang, Weiguang; Zhang, Donghan; Cheng, Ran; et al.
Abstract: Objectives: To search the behavioral effect of Gallbladder-warming Decoction with Bupleurum and Scutellaria (GWBS) on anxiety and depression model rats and explore its mechanism. Methods: Twenty SD rats were randomly divided into four groups with 5 in each group: blank control group, model group, weastern medicine group and GWBS group. The unpredictable chronic emotional stress method was used to induce anxiety and depression of model rats. Rats in weastern medicine group were given diazepam at 0.26 mg/kg/d and the 5 rats in GWBS group were given GWBS at 11.5g/kg/d, otherwise, the other two groups were given the same volume of normal saline once a day. The experiment lasted for 10 days, during which the general state including body weight, hair color, activity level and so on were observed and the data were recorded. The results of sucrose consumption test and the light-dark box test were also recorded during the ten days. After the experiment, the changes of histological pathologic in the hippocampus were examined, and the γ-aminobutyric acid concentration of the rat hippocampus was detected using ELISA kit. Results: Pathological results indicated that GWBS improved pyramidal cells in hippocampus keeping the disordered arrangement. In comparison of the model group, the body weights of the weastern medicine group and the GWBS group apparently increased. Besides, the retention time of the light box was significantly prolonged and the concentrations of γ-aminobutyric acid in the hippocampus were significantly promoted in the two groups. The differences above were with statistical significance (P<0.05). In addition, the sucrose consumption values were improved markedly. Conclusion: GWBS, the agent of relieving the depressed liver and resolving phlegm, makes a difference in treatment of anxiety and depression rats and its mechanism may be related to the increase of GABA concentration in hippocampus.